After Identity : Mennonite Writing in North America - Zacharias, Robert, 1977- (Book collections on Project MUSE., 2015)
"An interdisciplinary reappraisal of the field of Mennonite writing in Canada and the United States. Essays explore the unique configuration of religious and ethnic cultural difference"--Provided by publisher